THE EFFECT OF PERFORMANCE ALLOWANCES ON EMPLOYEE WORK MOTIVATION AT THE MEDAN CITY MINISTRY OF RELIGION OFFICE - Nasution, Lukman; Rizkina, Seila (Strategic Management Business Journal, 2024)
This research aims to determine the effect of performance allowances on employee work motivation at the Medan City Ministry of Religion Office. This study uses a quantitative approach. The population in this study were 30 employees of the Medan City Ministry of Religion Office. The data collection technique used was a questionnaire and then analyzed using simple linear regression analysis to test hypotheses, correlation analysis and coefficient of determination. However, previously validity and reliability tests were carried out. Based on the research results, there is a significant influence between performance allowances and work motivation. The Tcount value is 2,476 > Ttable value 2,048 and the significance value is 0.016 < 0.05. JEL Classification: L2, L25, M5